The unboxing of a Black girl - Shanté, Angela (Page Street Publishing Company, 2024)
"Set in New York City in the '90s, Angela Shanté's poems and stories paint a mosaic of childhood that is shaped by the past and reverberates into the present. As Shanté navigates the city through memory, this timeless book illuminates the places where Black girls are nurtured or boxed in, through stories and poems about expectations, exploitation, love, loss, and self-realization. Her poems center on pivotal moments of Black childhood, using footnotes that encourage you to listen to songs, watch movies, and even learn how to play Spades to further contextualize and celebrate Black culture in every aspect of life. But even with Black joy, life ain't no crystal stair. Between fond memories, Shanté also explores the dark corners of childhood by showing us the ways adultification, misogynoir, and sexual assault can impact girlhood. Every piece in this memoir invites you to unpack the past--to find and transcend the expectations and boxes the world puts Black girls in"--